BOZOR MUNOSABATLARI SHAROITIDA TALABALARNI IQTISODIY IJTIMOIYLASHTIRISHNING MOHIYATI - Tolepov, Е.T. (SCIENCE and SOCIETY, 2024)
Over the years of independence, a free market economy has been formed in Uzbekistan. The establishment of private property in society and the emergence of strong competition in the labor market require every citizen to have economic knowledge and skills. Consequently, awareness of economic knowledge ensures economically effective socialization of a person. The article is about ensuring the economic socialization of students in market conditions.
Keywords: market economy; economic relations; socialization; economic socialization; students; economic socialization of students